Seasonal and Inter Annual Variation of Sea Surface Temperature in the Indonesian Waters - Martono Martono (Universitas Muhammadiyah Surakarta, 2016)
Sea surface temperature plays an important role in air-sea interactions. This research was conducted to understand seasonal and interannual variations of sea surface temperature in the Indonesian waters. The data used in this research was daily sea surface temperature in 1986 to 2015 which was obtained from the Physical Oceanography Distributed Active Archive Center - National Aeronautics and Space Administration. Method used in this study was the anomaly analysis. The result showed that the seasonal and interannual variations of sea surface temperature in the Indonesian waters varied. Seasonal variations of SST in the Makasar Strait, Sulawesi Sea, and Halmahera Sea were low. High seasonal variations of sea surface temperature occurred in the southern waters of Java, Timor Sea, Arafura Sea, and Banda Sea, which were allegedly due to the upwelling process. In addition, interannual variation of sea surface temperature in the Indonesian waters fluctuated. From 1986 to 2000, it showed a negative anomaly dominant. Meanwhile, from 2001 to 2015, it showed a positive anomaly dominant. The effect of Indian Ocean Dipole on the fluctuation of sea surface temperature in the Indonesian waters was stronger than ENSO. Within the last 30 years, the sea surface temperature in the Indonesian water indicated a rising trend. The highest sea surface temperature rise occurred in the Halmahera Sea that reached 0.66 OC/30 years and the lowest was in the Timor Sea of 0.36 OC/30 years.